2007
DOI: 10.1007/s11214-007-9224-0
|View full text |Cite
|
Sign up to set email alerts
|

Astrophysics in 2006

Abstract: The fastest pulsar and the slowest nova; the oldest galaxies and the youngest stars; the weirdest life forms and the commonest dwarfs; the highest energy particles and the lowest energy photons. These were some of the extremes of Astrophysics 2006. We attempt also to bring you updates on things of which there is currently only one (habitable planets, the Sun, and the universe) and others of which there are always many, like meteors and molecules, black holes and binaries.Comment: 244 pages, no figure

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 2,049 publications
(1,289 reference statements)
0
8
0
Order By: Relevance
“…In addition to these four instrument teams, there are several groups devoted to global modeling (see Aschwanden et al 2007) with the goal of understanding the connection between the solar activity observed near the sun by SECCHI and S/WAVES and the in situ measurements taken by IMPACT, PLASTIC and S/WAVES when the disturbances finally reach the STEREO spacecraft. Modeling includes the coronal plasma and the solar wind and its expansion outwards from the Sun.…”
Section: • Stereo/waves (S/waves) Was Built By a Team Led By Jean-loumentioning
confidence: 99%
“…In addition to these four instrument teams, there are several groups devoted to global modeling (see Aschwanden et al 2007) with the goal of understanding the connection between the solar activity observed near the sun by SECCHI and S/WAVES and the in situ measurements taken by IMPACT, PLASTIC and S/WAVES when the disturbances finally reach the STEREO spacecraft. Modeling includes the coronal plasma and the solar wind and its expansion outwards from the Sun.…”
Section: • Stereo/waves (S/waves) Was Built By a Team Led By Jean-loumentioning
confidence: 99%
“…Kurtz, Eichhorn, Accomazzi, Grant, Demleitner, Murray, and colleagues (2005) pointed out that the series of papers by Trimble and colleagues: “Astrophysics in XXXX” (where XXXX is the immediate past year) each year is routinely the most used paper in astronomy, but is very rarely cited; for example, the most recent two, (Trimble, Aschwanden, & Hansen, 2006, 2007) have yet to be cited (as this is written). These papers are like newspapers in their usefulness.…”
Section: Usage Bibliometricsmentioning
confidence: 99%
“…However, in the Hubble flow the space itself expands with no centre. In a PN, there is a well‐defined centre of the expanding gas; see Trimble, Aschwanden & Hansen 2007. )…”
Section: Introductionmentioning
confidence: 99%